The Story of Prophet Salih - Khan, Saniyasnain, 1959- (New Delhi : Goodword Books, 2022)
This delightful board book is a perfect gift for little children. The Quran story of Prophet Hud and the great builders of Ad, comes with engaging illustrations, simple text and a moral in the end of the story.
Keywords: Prophets in the Qur'an -- Juvenile literature; Prophets, Pre-Islamic -- Juvenile literature; Islamic stories, English; Board book